Los teléfonos celulares y las prácticas de vigilancia en la pareja - Rodríguez Salazar, Tania (El Colegio de México, 2025)
Interpersonal surveillance practices in heterosexual couples through smartphones in couples are analyzed with an approach that combines a surveillance typology with game metaphors. Differences were found in the narratives concerning surveillance and being surveilled, revealing that these practices are embedded in interactions of concealment, pursuit, persecution, annihilation, or collaboration. The greater prevalence of control surveillance is highlighted, and a tendency toward tactical surveillance among women and strategic surveillance and self-surveillance among men is outlined. Likewise, care surveillance activities are observed that range from the authentic to the ambiguous, as well as participatory surveillance, which involves the participation of third parties to record transgressive acts.